Generalised interval‐based analysis tool for pattern distortions in reflector antennas with bump‐like surface deformations. Issue 9 (1st June 2016) - Anselmi, Nicola; Salucci, Marco; Rocca, Paolo; Massa, Andrea
Abstract : The prediction of the effects on the power pattern of bump‐like distortions in the surface of reflector antennas is addressed. The expressions of the upper and the lower bounds of the power pattern radiated by the deformed reflector are analytically derived by means of the interval analysis as a function of the uncertainty on the bump depth. A set of representative numerical results is reported and discussed to validate the effectiveness and the reliability of the proposed approach also in comparison with state‐of‐the‐art methods and commercial software based on statistical methods and physical optics, respectively.